A Critical Review of The Roman Historian Tacitus's Book of Annals - Yaser Malekzadeh; Sorour Khorashadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Roman historian Tacitus’ s Book of Annals is an important historical source on the history of the Parthians and their neighbors.  Although Mirsaidi’s, the translator, main focus is on Roman history, this book also has some very important mentions on the role of the Parthians and their subordinate lands, but they were not translated. In this work, a comparative study was conducted between the original English version of the book and its Persian translation to examine the accuracy of the content of the Persian translation. The authors have tried to review the translation of the book after introducing the main gist of the book and some of its important non-Persian editions and subsequently comparing these translations with its English translation. This reminds the value and/or issues related to the work, along with an emphasis on some neglected points in the Persian translation. The writers of this article have translated some parts of the book, which relates to Parthian history in Iberia and Armenia. Iranian and Parthian houses played an important role in these lands. These parts are not in the Mirsa’idi’s translation, but their history was in association with Parthian history in Persia.